Managerial Heuristics in Servitization Journey - Huikkola, Tuomas; Kohtamäki, Marko (Palgrave Macmillan, 2021)
This essay conceptualizes the role of managerial heuristics when manufacturers undergo service transition. The present conceptual article suggests that managers can learn different heuristics from experiences (e.g., trial-and-error) when transitioning toward services and solutions and discusses one missing element in the existing servitization literature: managerial heuristics and the use of simple rules to manage servitization and facilitate organizational learning (i.e., why, what, and how manufacturers learn when they servitize). This study encourages future studies to more broadly investigate the psychological foundations of the strategic change process in the context of servitization.
Keywords: Expert heuristics; heuristics; Psychological foundations of strategy; Servitization; Simple rules; fi=Strateginen johtaminen|en=Strategic Management|